Chapter Feeding inequalities: the role of economic inequalities and the urban market in late medieval food security. The case of fourteenth-century Ghent - Espeel, Stef (Datini Studies in Economic History, 2020)
Although the Food and Agricultural Organization (FAO) revised their theoretical model of food security for over two decades ago, historians have been slow in adopting these new insights to study pre-modern societies. Showcasing the potential of the holistic approach proposed by the FAO, this paper analyses the evolution of food security in the calamitous fourteenth century in Ghent, one the most populated cities at that time. In the long-term, access to food seem to have bettered during the second half of the century thanks to increased wages, wealth and investments into farmland. While these gains can partly be linked to demographic evolutions, we found no evidence of an often-hypothesized Malthusian ceiling before the Black Death.